The Comparison of Religiosity Level Between Students With “Niqab” and Students Without “Niqab” - Falikah, Tri Yaumil; Nuryana, Zalik; Kurniawan, Muh. Alif (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study intends to examine whether there is a difference in the level of religiosity between students with “niqab” and students without “niqab”. The discourse on wearing the “niqab”l is still a crucial problem in several educational institutions in Indonesia, including Universitas Ahmad Dahlan (UAD). Design/methods/approach – This is quantitative research at the Ahmad Dahlan University Islamic Education Study Program with a random sampling technique. The data collection tool used was a questionnaire with a Likert scale of scale 4. The instrument was tested with validity, reliability, normality, and homogeneity tests. The data were then analyzed by using the T-test to test the hypothesis. Findings – The results showed that the level of religiosity of female students with “niqab” at Pendidikan Agama Islam (PAI) UAD was in the high category. This was evidenced by 33 respondents of students with “niqab” at PAI UAD. 23 subjects (69.6%) showed a high religiosity and ten subjects (30.3%) were in the medium category. The religiosity of students without “niqab” at PAI UAD was also in the high category, as shown by 33 respondents who are without “niqab” at PAI UAD. There were 26 subjects (78.7%) showing a high level of religiosity, and seven subjects (21.2%)were in the medium category. Research implications/limitations – The analysis results showed that there was no difference in the level of religiosity between students with “niqab’ and students without “niqab” at PAI UAD, as evidenced by the t count = 0.452 (sig < 0.05) then Ha was accepted, and Ho was rejected. Originality/value – There is no difference in the level of religiosity between students with “niqab” and students without “niqab” in PAI UAD. “Niqab” is not part of Islamic shari'a so it cannot always be associated with one's religious experience. The nature of religiosity cannot be established simply by wearing the “niqab” without looking at other religious dimensions.